Association between Raised Serum IgE Levels and Bronchial Asthma in Children - Muhammad Rafiq Khan, Farhan Ali, Siddiqa Batool, Muhammad Afzal, Abdul Rahman Abid (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Studies of allergy and respiratory diseases have traditionally used allergy skin test reactivity, serum IgE levels or peripheral blood eosinophilia to identify atopic subjects. Objectives: The main objective of the study is to find the association between Raised Serum IgE levels and bronchial asthma in children. Material and methods: This cross sectional study was conducted in Independent Medical College FSD during June 2020 to June 2021. The data was collected from 140 patients of age range 2 to 12 years. Each patient was thoroughly examined by the physician and the proforma was filled accordingly. Results: The data was collected from 140 patients. The results showed no significant associations of gender, family history of asthma, exclusive breastfeeding up to 6 months and residential set up with the elevated level of total serum IgE. The higher age group, exposure to cigarette smoke and the raised eosinophil count showed the significant associations with the elevated levels of total serum IgE in asthmatics. Conclusion: It is concluded that total serum IgE tracks with age, children who are predisposed to persistent wheezing and early sensitization to local aeroallergens already have high levels of IgE. Serum total IgE level is a good predictor of allergy in children.